Fathers’ sensitive guidance moderates the association between coparenting and behavioral regulation in preschoolers - Baptista, J.; Sousa, D.; Soares, I.; Martins, C. (International Journal of Behavioral Development, 2018)
The purpose of this study was to determine the links between paternal sensitive guidance, coparenting, and child behavioral regulation. It also aimed to assess whether paternal sensitive behaviors moderate the putative relationship between cooperative coparenting and child regulatory abilities. The sample comprised 70 preschoolers and their fathers. Behavioral regulation was assessed using the Head–Toes–Knees–Shoulders task. For the assessment of paternal sensitive guidance, dyads were videotaped during a picture-book reading task. Fathers reported coparenting cooperation. Results revealed that coparenting predicted behavioral regulation, even after accounting for verbal ability and parental education. No significant links emerged between fathers’ sensitive guidance and regulatory skills. However, the interaction of coparenting and paternal sensitive behaviors predicted behavioral regulation: a lower score on cooperative coparenting was linked to more regulatory difficulties, when coupled with lower levels of paternal sensitive guidance. Intervention programs, designed to promote child self-regulation, should be focused on strategies aimed to improve both the cooperation between parents and the quality of individual parenting. Efforts should be made to include fathers.